PROGRAM PEMBERDAYAAN DESA (STUDI KASUS UED-SP DHARMA BAKTI DESA GABUNG MAKMUR KABUPATEN SIAK) - Lumban Gaol, Million; Rusli SD, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Village Empowerment Program The program is aimed to review penangulangan Accelerate Poverty through Economic Empowerment UED-SP WITH provision Against Pemanfaat / or rural communities What do loans for a review of the business, Institutional Capacity and Empowerment AT village UED-SP. to review meujudkan Village Community Development The participatory and self-reliant. Of Research Singer substance is to determine the extent of development review UED-SP Dharma Bakti And The agency encourages empowerment hearts IN Village Community Economic businesses.Concept Theory The researchers use is empowerment Economic empowerment Institutional Capacity Productive And UED-SP Dharma Bakti. Methods used hearts singer research is qualitative descriptive WITH data collection instruments include Interview, Observation and Data Documents UED-SP Dharma Bakti.Research results show that the singer their taxable income through Empowerment Program Fund revolves UED-SP Dharma Bakti, the empowerment of society and Institutional capacity is increasing. ON refund arrears OR Loans Still experiencing congestion due to lack of training and mentoring Against USE Loan funds UED-SP Dharma Bakti. In addition to ITU, socioeconomic factors Pemanfaat The majority is Farmers, mostly oil, the price of palm fruit bunches (FFB) The fluaktif and social conditions laiinnya Opt Against Giving effect of economic business development Pemanfaat And Institutions UED-SP Dharma Bakti.Keywords: Poverty, Empowerment, UED-SP.